Influence of Roughness on Isothermal Elastohydrodynamic Lubrication of Roller Enveloped Worm Drive - Yan Qi; Honghui Liao; Xudong Wang; Zaixin Liu; Jinkuan Li (Jixie chuandong)
Based on the meshing principle of the roller enveloped end face worm drive pair， the influence of the center distance， the roller radius， the throat coefficient， and the worm gear diameter are considered comprehensively. According to the elastohydrodynamic lubrication theory， the Newton iteration method is used in Matlab. The Newton-Raphson method is used to solve its numerical calculation， the conjugate teeth of the new transmission pair are studied， and the analysis of the line contact between the conjugate teeth is completed. The schematic diagram of lubricating oil film pressure and oil film thickness under the change of geometric parameters and roughness amplitude of the conjugate tooth surface of the transmission pair is given， and the analysis is completed. The results show that the performance of the transmission pair is good. The important parameters affecting the lubrication are the roller radius and the meshing position， while the throat coefficient and the worm gear diameter have little effect on the lubrication characteristics. Full-film lubrication can be generated between the conjugated tooth surfaces to avoid direct contact， reduce wear and oil temperature， and improve transmission efficiency and anti-glue ability at the same time. Therefore， the necessary theory and application value are given for the development of the new transmission pair.